1994
DOI: 10.1007/bf00202818
|View full text |Cite
|
Sign up to set email alerts
|

Acute intermittent porphyria caused by a single base insertion of C in exon 15 of the porphobilinogen deaminase gene that results in a frame shift and premature stopping of translation

Abstract: A single base insertion of C in exon 15 of the porphobilinogen deaminase (PBG-D) gene was observed in a patient with acute intermittent porphyria (AIP) by polymerase chain reaction (PCR)-direct sequencing analysis. The insertion locates between positions -22 and -21 from the translation termination codon TAA, causes a frame shift, and results in a stop codon located 4 codons downstream from the insertion (premature stopping of translation). The mutation generates an MspI recognition site, which can be used, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
7
0

Year Published

1995
1995
2002
2002

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 16 publications
1
7
0
Order By: Relevance
“…In Japan, five kinds of mutations in the HMBS gene have been described in six unrelated Japanese families so far (Daimon et al 1993;Daimon et al 1994;Morita et al 1995;Tomie et al 1998;Maeda et al 1999) (Fig. 4), with four of the families having the same mutations as those reported in Europe.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…In Japan, five kinds of mutations in the HMBS gene have been described in six unrelated Japanese families so far (Daimon et al 1993;Daimon et al 1994;Morita et al 1995;Tomie et al 1998;Maeda et al 1999) (Fig. 4), with four of the families having the same mutations as those reported in Europe.…”
Section: Discussionmentioning
confidence: 90%
“…In Japan, however, molecular analyses have been documented in only six families (Daimon et al 1993;Daimon et al 1994;Morita et al 1995;Tomie et al 1998;Maeda et al 1999) to date.…”
Section: Introductionmentioning
confidence: 99%
“…Although high prevalences have been reported for two mutations as the result of a founder effect (Lee et al, 1990;Lee and Anvret, 1991 ;Gu et al, 1993), many of them were found only in very few families, indicating that AIP is very heterogeneous at the molecular level. Up to now, two mutations were reported in Japanese patients (Daimon et al, 1993(Daimon et al, , 1994, and those were not reported yet in any other population. We report in this manuscript another mutation of the gene found in a Japanese patient.…”
mentioning
confidence: 88%
“…To date, more than 30 different mutations have been reported (Daimon et al, 1993(Daimon et al, , 1994Delfau et al, 1990Delfau et al, , 1991Grandchamp et al, 1989a-c;Gu et al, 1992Gu et al, , 1994Scobie et al, 1990;Lee and Anvret, 1991;Lee et al, 1990;Llewellyn et al, 1992;Lundin et al, 1994;Mgone et al, 1992Mgone et al, , 1993Schreiber et al, 1994). Although high prevalences have been reported for two mutations as the result of a founder effect (Lee et al, 1990;Lee and Anvret, 1991 ;Gu et al, 1993), many of them were found only in very few families, indicating that AIP is very heterogeneous at the molecular level.…”
mentioning
confidence: 99%
See 1 more Smart Citation